Persepsi Nelayan Jaring Tarik Berkantong Terhadap Implementasi Logbook Penangkapan Ikan Di Pelabuhan Perikanan Kluwut - Rizqi Isticharoh; Sri Mulyani; Heru K. Alamsyah (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
The capture fisheries sector requires data-based management to support the sustainability of fishery resources. One of the efforts is the implementation of fishing logbooks as regulated in the Minister of Marine Affairs and Fisheries Regulation No. 33 of 2021. This study aims to analyze fishermen’s perception of the implementation of fishing logbooks among danish seine fishermen. The research was conducted from December 2025 to January 2026 at Kluwut Fishing Port, Brebes Regency. This study used a mixed method approach with data collection techniques including observation, interviews, and documentation. Data analysis was carried out using Likert scale, validity and reliability tests, and multiple linear regression with SPSS. The results showed that fishermen’s perception of logbook implementation was in the moderate category with a value of 51%. Regression analysis indicated that knowledge of logbook regulations, logbook filling procedures, and E-logbook usage significantly influenced knowledge of logbook benefits. The main constraints faced by fishermen include low technological literacy and limited use of digital devices and internet networks in supporting E-logbook implementation.